Primarna odpornost bakterije Helicobacter pylori - Jeverica, Samo (Zdravniški vestnik, 2010)
Background: Antimicrobial resistance, particularly against metronidazole and clarithromycin, is the leading cause for treatment failure of Helicobacter pylori infection. Eradication rates of primary therapy have fallen below 80% in the majority of states including Slovenia. Th e aim of the study was to assess primary resistance to key antibiotics used for eradication treatment. Patients and methods: Between 2007 and 2009 we isolated 97 strains of Helicobacter pylori from the treatment naive patients who have not previously underwent eradication treatment. Antimicrobial susceptibility testing was doneusing phenotypical methods. Etests and breakpoint agar dilution method formetronidazole. We analyzed resistance profi les of the isolated bacteria and presenteddistribution of different phenotypes of Helicobacter pylori. Results: Th e primary antimicrobial resistance for metronidazole and clarithromycin was 18.6% and 17.5%, respectively. Combined resistance for bothmetronidazole and clarithromycin was 4.1%. In our group of isolates we didnot fi nd any resistance against amoxicillin and tetracycline. 3.1% of isolates were ciprofl oxacin resistant. Conclusions: Systematic surveillance of antimicrobial resistance of Helicobacter pylori is mandatory to adjust primary and subsequent eradication therapy. Performing antimicrobial susceptibility testing is a costly method and that is why it is important to fi nd resources to make it possible.
Keywords: antibiotic; antibiotiki; bacteria; bakterije; Clarithromycin; Drug Resistance, Microbial; Drug Therapy; Helicobacter Infections; Helicobacter Pylori; Helicobacter, infekcije; Immunology; Klaritromicin; Metronidazol; Metronidazole; Microbial Sensitivity Tests; Mikrobni, občutljivostni testi; odpornost; Zdravilo, rezistenca mikrobna